DETERMINATION OF PROGNOSTIC CRITERIA OF CARDIORESPIRATORY SYSTEM DYSADAPTATION IN PREGNANT WOMEN WITH HIGH OBSTETRICAL RISK AND COMPLICATED COURSE OF PREGNANCY - I. V. Sokolnikova; V. P. Khokhlov (Acta Biomedica Scientifica, 2012)
The article reviews the indices of cardiorespiratory system adaptation, obtained, at the performing the test with, graduated, physical exercise in pregnant women with. high, obstetrical risk, that can be used, as prognostic criteria of development of pregnancy course complications.